A 38 Years Old Man with ANCA Negative Wegener’s Granulomatosis Vasculitis with Type 2 Diabetes Mellitus and Electrolyte Imbalance: A Case Report: ANCA Negative Wegener’s Granulomatosis Vasculitis - Bryan Arief Aji Rudita; Yulyani Werdiningsih; Arief Nurudhin; Nurhasan Agung Prabowo; Zainal Arifin Adnan (Indonesian Journal of Rheumatology, 2020)
A B S T R A C TBackground: Wegener's granulomatosis is a very rare long-term systemicdisorder, in which granuloma formation occurs and inflammation of bloodvessels (vasculitis). The cause of disorder is not yet known, but geneticfactors are thought to play an important role. Clinical symptoms are oftensimilar to other disorders, making diagnosis difficult. However, earlydiagnosis is very important in order to provide effective management.Objective: Diagnosis and management in a rare case of Wegener’sgranulomatosis vasculitis, especially it was found with other comorbidities.Methods: This case report showed a-38-years-old-man that came to theemergency room of Dr Moewardi Hospital with complaints of swellingaccompanied by redness and stiff on the face, hands and feet that worseningsince 7 days ago. He also complained of fever fluctuating, nasal congestionaccompanied by clear discharge and sometimes hearing loss in the rightear. Since the last 3 months, he was often experience similar complaints.History of diabetes was recognized by the patient for 5 years, but he did notregularly take medication. Results: In this case, examination of vital signswithin normal limits. Physical examination revealed a saddle nose with cleardischarge, swelling and redness around the face, hands and feet. Laboratorytests showed hemoglobin 12.9 g/dl, HbA1c 8.4%, sodium level 128 mmol/L,potassium level 3.1 mmol/L, calcium level 1.12 mmol/L. The Anti -Neutrophil Cytoplasmic Antibodies (ANCAs) and Anti Nuclear Antibody(ANA) Indirect Immunofluorescence (IF) method were negative.Electrocardiogram and chest x-ray examination within normal limits.Histopathological examination revealed epidermal atrophy and multiplegranulomas of the dermis. The patient underwent treatment for 10 dayswith tappering-off dose steroid, immunosuppressants, insulin, calcium,and potassium preparations therapy. Conclusions: Wegener’sgranulomatosis vasculitis is a rare case. Prompt and accurate diagnosis andmanagement will prevent poor progression of them, especially it was foundwith other comorbidities.